2014
DOI: 10.1152/ajprenal.00114.2014
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial damage and vascular calcification in patients with chronic kidney disease

Abstract: Carracedo J. Endothelial damage and vascular calcification in patients with chronic kidney disease. Am J Physiol

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 43 publications
(51 reference statements)
0
61
0
7
Order By: Relevance
“…Activated endothelial cells in uremia are capable of producing microparticles that induce OC expression in endothelial progenitor cells, VSMCs and fibroblast. The imbalance in the process of endothelial damage and repair, therefore, may contribute to VC via increasing the number of OC-positive endothelial progenitor cells [34]. …”
Section: Discussionmentioning
confidence: 99%
“…Activated endothelial cells in uremia are capable of producing microparticles that induce OC expression in endothelial progenitor cells, VSMCs and fibroblast. The imbalance in the process of endothelial damage and repair, therefore, may contribute to VC via increasing the number of OC-positive endothelial progenitor cells [34]. …”
Section: Discussionmentioning
confidence: 99%
“…diabetes, kidney disease, atherosclerosis and coronary artery diseases) endothelial damages are also associated with vascular calcification [22]. It has been demonstrated that procalcific polarization of circulating progenitors may contribute to vascular mineralization in patients exhibiting a calcifying potential in vitro [9,23].…”
Section: Discussionmentioning
confidence: 99%
“…Circulating MPs have been the most studied EVs in humans with CKD and ESRD, conditions in which MPs have been associated with endothelial dysfunction, 67 cardiovascular mortality, 68,69 increased risk for calcification, 70,71 anemia, 72,73 and disease-specific alteration in coagulation. 74 In a study of a heterogeneous group of patients with chronic renal failure and those on peritoneal dialysis and hemodialysis, all patients compared with healthy controls had higher levels of endothelial-derived microparticles (EMPs) and MPs of leukocyte origin.…”
Section: Ckd/uremia/esrdmentioning
confidence: 99%